Variation of hydrogeochemical characteristics of water in surface flows, shallow wells, and boreholes in the coastal city of Douala (Cameroon). Issue 16 (9th December 2016) - Fantong, Wilson Y.; Kamtchueng, Brice T.; Ketchemen-Tandia, Beatrice; Kuitcha, Doris; Ndjama, Josephine; Fouepe, Alain T.; Takem, Gloria E.; Issa,; Wirmvem, Mengnjo J.; Djomou, Serges L. Bopda; Ako, Andrew A.; Nkeng, George E.; et al.
ABSTRACT: Groundwater is used by 3 million inhabitants in the coastal urban city of Douala, Cameroon, but comprehensive data are too sparse for it to be managed in a sustainable manner. Hence this study aimed to (1) assess the potability of the groundwater; (2) evaluate the spatial variation of groundwater composition; and (3) assess the interaction and recharge mechanisms of different water bodies. Hydrogeochemical tools and methods revealed the following results in the Wouri and Nkappa formations of the Douala basin, which is beneath Douala city: 30% of water samples from hand-dug wells in the shallow Pleistocene alluvium aquifer were saline and highly mineralized. However, water from boreholes in the deeper (49–92 m depth) Palaeocene aquifer was saline-free, less mineralized and potable. Water in the shallow aquifer (0.5–22 m depth) was of Na + -K + -Cl − -NO3 − type and not potable due to point source pollution, whereas Ca + -HCO3 − unpolluted water dominates in the deeper aquifer. Water in the deep and shallow aquifers indicates the results of preferential flow pass and evaporative recharge, respectively. Possible hydrogeochemical processes include point source pollution, reverse ion exchange, remote recharge areas and mixing of waters with different chemical signatures.EDITOR D. KoutsoyiannisASSOCIATE EDITOR M.D. Fidelibus